Individual labour rights as human rights: the contributions of the European Court of Human Rights to worker's rights protection - Sychenko, Elena (The Hague, 2017)
"Bulletin of Comparative Labour Relations Volume 96 In recent years there has been a substantial debate over the interconnection between labour rights and human rights. Consequently, the jurisprudence of the European Court of Human Rights (ECtHR) concerning substantive individual labour rights, or 'rights at work', is coming to greater prominence at the national level throughout the forty-seven Member States of the Council of Europe. This is the first book in English to provide a thorough analysis of the Court's most recent case law - cases considered in the period from 1963 to 2016 - on fundamental employment rights such as the right to wages, protection from discrimination and unfair dismissal, the right to occupational safety at work, and civil liberties such as the freedom of association, the freedom of religion and expression, and the right to privacy. Drawing on close scrutiny of 347 cases since 1963, the author traces the evolutionary development of the Court's positions on labour rights as human rights through case analyses, commentary, and general conclusions in each of several categorical groupings. Recent trends are treated in substantial detail. Among the issues and topics raised are the following: interrelation of ECtHR case law and national labour rights protection; benefits for employees of reference to ECtHR case law in national proceedings; role of International Labour Organization conventions and of the European Social Charter in the Court's reasoning; application of balancing and proportionality test in relevant to labour law cases; public criticism of employer, disclosure of information, and standards of whistle-blowers' protection; and positive obligations of the State in the field of occupational safety and health. This book offers the most detailed and considered analysis available of how individual labour rights have been referred to in the human rights jurisprudence of the ECtHR. Given that the Court's positions have already changed certain aspects of some national labour laws, this peerless volume will prove indispensable for practitioners and scholars monitoring the growing applicability of human rights law in matters of labour and employment, especially in the areas of protection of wages, unjust dismissal, and occupational safety."